Students’ Narrative Writing : An Error Analysis - Indah Khairunnisa; Shynta Amalia; Rizqy Dwi Amrina (English Education Department at FKIP Nommensen University, 2023)
The objective of this research was to investigate the kinds of errors on using simple past tense in writing narrative text at ninth grade students at SMP N 4 Rambutan. The research design used in this study was quantitative descriptive. The sampling technique to choose 1 class which consist of 30 students were used cluster random Sampling . The data was collected through students' writing task. After got the data, the results of this study showed that there were errors made by students in the use of the simple past tense. The errors are categorized into 4, consisting of omission, misformation, addition, and misordering. First, there are 39 or 31.70% omission. Second, there are 69 or 56.09% misformation. Third, there are 11 or 8.94% addition. Finally, there are 4 or 3.25% misordering. In summary, misformation is the most dominant type of error that appeared in students' narrative text writing.